Systematic scoping review of the noma evidence landscape: current knowledge and gaps - Prabin Dahal; Philippe J Guérin; Elinor Harriss; Yuka Makino; Brittany J Maguire; Rujan Shrestha; Roland Ngu; Lionel Nizigama; Sumayyah Rashan; Poojan Shrestha; Paul Newton; Benoit Varenne (BMJ Global Health)
Background Noma (cancrum oris) is a severe gangrenous disease of the mouth and oro-facial structures. Noma often affects young children living in extreme poverty, malnutrition and poor sanitation. Gaps remain in understanding its aetiology, pathogenesis, prevention and treatment.Methods and findings We systematically searched databases for all primary research studies (clinical trials, cohort studies, case–control, cross-sectional, other observational studies, case studies/series) reporting noma patients of any age up to 7 December 2022. The 366 publications (published between 1839 and 2022) included in our scoping review describe 15 082 patients. Although 53 cohort and 29 cross-sectional studies were identified, enrolling 13 489 patients, interventional research remains extremely limited, with only six studies identified (101 patients, range: 7–26) and only one in the past decade, highlighting a critical gap in treatment evaluation. A total of 380 different treatment modalities were described, which underscores lack of a standardised practice. Disease aetiology remains unclear, with 117 microorganisms reported across 113 studies, yet none more consistently linked to noma development. Since 2000, 91.2% of cases have been reported in Sub-Saharan Africa, though occurrences outside the ‘noma belt’ and into Asia and the Americas suggest a broader risk. The 212 potential risk factors identified in 269 (73.5%) publications reflect substantial heterogeneity, complicating efforts to determine definitive causative factors. Additionally, the inconsistent definition and reporting of noma staging significantly hinder comparability across studies, with wide adoption of the WHO staging classification needed.Conclusion This comprehensive review of the literature underscores the urgent need for robust, policy-driven research to address the vast knowledge gaps in the physiopathology of noma and the limited evidence currently available to guide therapeutic and preventive policies. Collective action and increased research investment are crucial, especially now that noma is officially recognised as a neglected tropical disease by the WHO.